Conversational adaptation in children and teens with autism: Differences in talkativeness across contexts. Issue 6 (24th February 2022) - Cola, Meredith; Zampella, Casey J.; Yankowitz, Lisa D.; Plate, Samantha; Petrulla, Victoria; Tena, Kimberly; Russell, Alison; Pandey, Juhi; Schultz, Robert T.; Parish‐Morris, Julia
Abstract: Successful social communication is complex; it relies on effectively deploying and continuously revising one's behavior to fit the needs of a given conversation, partner, and context. For example, a skilled conversationalist may instinctively become less talkative with a quiet partner and more talkative with a chattier one. Prior research suggests that behavioral flexibility across social contexts can be a particular challenge for individuals with autism spectrum condition (ASC), and that difficulty adapting to the changing needs of a conversation contributes to communicative breakdowns and poor social outcomes. In this study, we examine whether reduced conversational adaptation, as measured by talkativeness, differentiates 48 verbally fluent children and teens with ASC from 50 neurotypical (NT) peers matched on age, intelligence quotient, and sex ratio. Participants completed the Contextual Assessment of Social Skills with two novel conversation partners. The first acted interested in the conversation and talked more (Interested condition), while the second acted bored and talked less (Bored condition). Results revealed that NT participants emulated their conversation partner's behavior by being more talkative in the Interested condition as compared to the Bored condition ( z  = 9.92, p  < 0.001). In contrast, the ASC group did not differentially adapt their behavior to the Bored versus Interested context, instead remaining consistently talkative in both ( p  = 0.88). The results of this study have implications for understanding social communication and behavioral adaptation in ASC, and may be valuable for clinicians interested in improving conversational competence in verbally fluent individuals with autism. Lay Summary: Social communication—including everyday conversations—can be challenging for individuals on the autism spectrum. In successful conversations, people tend to adjust aspects of their language to be more similar to their partners'. In this study, we found that children and teens with autism did not change their own talkativeness in response to a social partner who was more or less talkative, whereas neurotypical peers did. These findings have clinical implications for improving conversational competence in verbally fluent individuals with autism.